Multimodal Analysis of Masculinity Portrayed in Digital Picture Books in www.storybookscanada.ca - Muhammad Nauval; Leni Marlina (Universitas Negeri Padang, 2023)
Picture books as a discourse combine both verbal and visual in order to deliver the event of the story. This research aims to analyze how attributes of masculinity were presented in picture books. The verbal text and visual illustration is analyzed in six picture books which are Tom the Banana Seller, Magozwe, and Simbegwire. The visual analysis applied the narrative process of representational meaning by Kress and Van Leeuwen, while the verbal analysis applied the experiential functions of systemic functional linguistics experiential function by Halliday. The data used in this research were the illustration and narration text which contain attributes of masculinity. The methodology applied in this research is descriptive qualitative. Multimodal analysis is defined as an analysis technique which focuses on analyzing in more than one mode. The results in this research show there are 14 illustrations and 17 narration texts that contain the attributes of masculinity. The dominant narrative process used to present the attribute of masculinity is actional transactional process. While the dominant experiential functions used to present the attribute of masculinity is material process.